THE INFLUENCE OF ACADEMIC SERVICE QUALITY ON STUDENT SATISFACTION AT PUSMANU PEKALONGAN POLYTECHNIC - Singgih Setiawan; Jilma Dewi Ayuningtyas (Politeknik Negeri Semarang, 2022)
This study aims to examine the effect of Physical Evidence (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) and Empathy (X5), on Student Satisfaction (Y). To test these variables, the researcher chose the campus as the research object. The research was conducted by distributing questionnaires to 100 students of the Pusmanu Pekalongan Polytechnic. The research sample was taken using the Stratified Random Sampling technique. The results showed that Physical Evidence (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) and Empathy (X5) had a significant positive effect on Student Satisfaction (Y) at the Polytechnic Pusmanu Pekalongan. But Assurance (X4) and Empathy (X5) are variables that have a strong influence on Student Satisfaction (Y) at Pusmanu Pekalongan Polytechnic.